Comparison study of spherical and multi-spherical particles under cyclic uniaxial compression - Tumonis, Liudas; Kačianauskas, Rimantas; Norkus, Arnoldas; Žilionienė, Daiva (Journal of Civil Engineering and Management, 2012)
Numerical simulation of cyclic compression of granular material by performing oedometric test has been performed. Discrete Element Method (DEM) has been employed for simulation. A comparison study has aimed to examine the differences in macroscopic behaviour of material discretized by spherical (S) and non-spherical shape models of a particle. During the study, microscopic data of sand from Klaipėda were used for modelling the shape of particles. The nonspherical particles were described by multi-spherical (MS) models retaining distributions for size and aspect ratios. Two DE models of tested specimens were developed and the deformation behaviour under cyclic uniaxial compression was simulated numerically by applying the commercial EDEM code. The variation of the oedometric elasticity modulus was investigated and influence of particle shape on void ratio changes was demonstrated. It was clearly shown that application of S particles is much more sensitive to rearrangement of particles during densification DEM. Simulations illustrated that the elasticity modulus of material corresponding to MS particles is approximately 1.9 times larger comparing with material corresponding to S particles. Therefore, one must improve the magnitude of elasticity modulus by introducing a respective correction factor.